Caught off guard by opportunity: Disentangling the family-business nexus in the process of selling family business - Věra Králová; Pavel Král; Lucie Klattová (Contemporary Economics, 2025)
Family business literature is oriented toward intra-family succession as the preferred way to transfer businesses. However, when it comes to family business sales, neither the family business nor the acquisition literature provides sufficient knowledge about the sales process. This study aims to provide an in-depth exploration of family business sales from the seller's perspective and scrutinize how the family-business nexus, the idiosyncratic interconnection of family and business, evolves in the family business sale process. The longitudinal case study research design draws from a unique opportunity to study the entire family business sales process in a small family organization. Data from observations, interviews, internal documents, and communication were analyzed following grounded theory principles. The findings identify critical family- and business-dominated milestones in the process of selling a family business. The final model explains how a single commitment to a family business disentangles into a decreased commitment to business continuity and an increased commitment to family continuity owing to shifts in the driving criteria and goals of the sale. The findings extend the literature on family business sales and demonstrate how the family-business nexus impacts the sales process. Additionally, the shift in the seller's approach from family business sustainability (courtship) to direct financial profit (takeover) shifts the acquisition literature forward by revealing the dynamics of the business's selling approach.
Keywords: G34; L26; 330; family business sale; family business buyout; continuation commitment; takeover; courtship